2019
DOI: 10.32596/ejcm.galenos.2019.00004
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Rheumatic Heart Disease Patients to Secondary Prophylaxis and Main Reasons for Poor Adherence at Jimma Medical Center

Abstract: Objectives: Rheumatic heart disease (RHD) is the major long-term sequel of acute rheumatic fever (ARF), which involves the cardiac valves leading to stenosis or regurgitation with resultant hemodynamic disturbance. The incidence of ARF and prevalence RHD in the sub-Saharan Africa including Ethiopia are amongst the highest in the world. The main priority of long-term management of ARF or RHD is to ensure that patients are adherent to the secondary prophylaxis which is monthly benzathine penicillin injection to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…This finding was almost comparable with Pelajo et al, who reported an adherence rate of 65% among RHD patients in Brazil. 31 However, our figure was considerably higher than that found by Sayed (29.5%), 44 Thompson et al (48.7%), 48 Prasad et al (50%), 46 Musoke et al (54%), 53 Gasse et al (54%), 38 Mohammed et al (55.2%), 29 Huck et al (58%), 43 and Harrington et al (59%). 34 On the other hand, it was considerably less than of Saxena et al (93.6%), 52 Culliford-Semmens et al (92%), 54 Kumar et al (90%), 45 Mekonnen et al (80.6%), 37 and Sial et al (73.5%).…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…This finding was almost comparable with Pelajo et al, who reported an adherence rate of 65% among RHD patients in Brazil. 31 However, our figure was considerably higher than that found by Sayed (29.5%), 44 Thompson et al (48.7%), 48 Prasad et al (50%), 46 Musoke et al (54%), 53 Gasse et al (54%), 38 Mohammed et al (55.2%), 29 Huck et al (58%), 43 and Harrington et al (59%). 34 On the other hand, it was considerably less than of Saxena et al (93.6%), 52 Culliford-Semmens et al (92%), 54 Kumar et al (90%), 45 Mekonnen et al (80.6%), 37 and Sial et al (73.5%).…”
Section: Discussioncontrasting
confidence: 63%
“…RHD patients were regarded as having good adherence when the rate of adherence to secondary prophylaxis was ≥80% of the expected injections (if injected more than ten times per year) while good adherence was egarded as the patient missing prophylaxis at least three times per year. 29 , 36 , 49 In Ethiopia, adherence to secondary prophylaxis is focused to eradicate/prevent the disease by promoting injections for patients every 4 weeks. 50 Benzathin penicillin G injection is given, in accordance with the WHO 2003 guideline recommendation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…But, the predisposing condition to RHD (strep throat) is considered as a mild, self-limiting illness by most of the communities, especially in developing countries. Health seeking behavior and adherence to primary or secondary prevention of RHD remain low in those countries [ 13 - 16 ]. As a result, about 84% of RHD cases and 80% of estimated deaths are contributed from Africa, South-East Asia and Western Pacific regions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with that observed (23%) in a similar study conducted in past. 20 However, Sheron et al reported that 75% of children and 50% of adults missed their appointments because of fear of painful injections. 21 Several measures can be taken to reduce the pain.…”
Section: Discussionmentioning
confidence: 99%